2001
DOI: 10.1021/ic000867y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-P,N Aminophosphines and Coordination Chemistry to PdII. X-ray Structures of [PdCl2(Ph2PCH2CH(Ph)NHPh-κPN)] and [PdCl(η3-C3H5)(Ph2PCH2CH(Ph)NHPh-κP)]

Abstract: The reaction of the C=N bond in PhCH=NPh with the carbanionic species Ph2PCH2-, leading to the N-phenyl beta-aminophosphine Ph2PCH2CH(Ph)NHPh, L1, is described. This molecule reacts with different organic electrophiles to afford related compounds Ph2PCH2CH(Ph)NPhX (X = SiMe3, L2; COPh, L4), [Ph2MePCH2CH(Ph)NHPh]+(I-), L3, and [Ph2PCH2CH(Ph)N(Ph)CO]2, L5, containing two amido and two phosphino functions. The coordination properties of L1, L2, and L4 have been studied in palladium chemistry. The X-ray structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
(128 reference statements)
3
28
0
Order By: Relevance
“…The coordinated 1,5-COD (1,5-cyclooctadiene) C and H nuclei are labeled from 1 to 8, C 1 and C 2 being trans to P. ) (γ-P,N-1), and Ph 2 P(o-C 6 H 4 -CH 2 NHPh) (γ-P,N-2) were prepared according to literature. [13,14,17,[41][42][43][44] The synthesis of complex [RhCl(COD)(α-P,N)] 1 with α-P,N=Ph 2 PCH(o-C 6 H 4 Cl[Cr(CO) 3 ])NHPh has previously been described. [18] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinated 1,5-COD (1,5-cyclooctadiene) C and H nuclei are labeled from 1 to 8, C 1 and C 2 being trans to P. ) (γ-P,N-1), and Ph 2 P(o-C 6 H 4 -CH 2 NHPh) (γ-P,N-2) were prepared according to literature. [13,14,17,[41][42][43][44] The synthesis of complex [RhCl(COD)(α-P,N)] 1 with α-P,N=Ph 2 PCH(o-C 6 H 4 Cl[Cr(CO) 3 ])NHPh has previously been described. [18] …”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we have developed different pathways to chiral α-or β-P,N and mixed α,β-and β,γ-N,P,N ligands and their coordination properties have been explored in palladium() and rhodium() complexes. [13][14][15][16] Particularly, we have reported that β-P,N ligands adopt a chelating mode whereas α-P,N ligands are only P-coordinated in Cu I or in Rh I complexes. [17,18] Separate work has shown that β-P,N ligands in Rh I complexes can adopt a monodentate κ 1-P- [19] or a κ 2 -P,N-coordination mode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when a pyridinylphosphane is only P-coordinated in a Pd II complex, the dangling amine function acts then as a "proton messenger" in alkyne methoxycarbonylation catalysis, [2] whereas a selective P,N chelation of a chiral phosphanediamine induces an effective chiral field in the rhodium complex leading to a higher selectivity in asymmetric hydrogenation of acrylic acid. [7] In our laboratory, we have developed different access ways to chiral α- [11] or β-P,N [12,13] and mixed α,β-and β,γ-P,P,N [14] ligands and their coordination properties have been explored in copper(), [15] palladium(), [13,16] and rhodium() complexes [14,17,18] Recently, we have examined the co- and PhCD(CH 2 D)CHO (α,β-D 2 ) were also produced. This result suggests a reversible deprotonation assisted by an intramolecular H-bonding interaction between the dangling ammonium function and the carbonyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…The relative amounts of the various products were quantified by integration of the 13 C{ 1 H} resonances affected by the secondary isotope shift, since the Overhauser effect does not depend on the substitution pattern at the adjacent C atom. [32][33][34] Thus, for instance, the relative proportion of compounds PhCH(CH 3 )CHO and PhCH(CH 2 D)CHO were obtained by integration of the two proton-decoupled methyne signals, whereas the relative proportions of compounds PhCH(CH 3 )CHO and PhCD(CH 3 )CHO were obtained by integration of the two proton-decoupled methyl signals.…”
Section: Introductionmentioning
confidence: 99%
“…[29] This study highlighted a diastereoselective N-coordination in the cationic complex [Pd(η 3 -C 3 H 5 )(L 1 )]ϩ, and an NϪH···ClϪM intramolecular interaction involving the dangling NϪH moiety for the neutral complex [PdCl(η 3 -C 3 H 5 )(κ1:P,L 1 )]ϩ (see Figure 2) which is a feature of P-coordinated aminophosphanes with a secondary amine function. [30] We report here the extension of our synthetic procedure to a new β-aminophosphane and to its cationic allylpalladium complexes, including ones with asymmetric mono- substituted allyl ligands, as well as a detailed 2-D NOESY NMR investigation of the mechanism of interconversion of the various diastereomers.…”
Section: Introductionmentioning
confidence: 79%